Analysis of The Application of 3D Printing To Design A Water Thruster Jet Boat - LAZUARDI, LAZUARDI; Maryono Maryono; Sugeng Hadi Susilo; Muhammad Akhlis Rizza (Evrimata: Journal of Mechanical Engineering, 2024)
This study analyzes the application of 3D printing technology in designing and building a water jet propulsion for boats. 3D printing technology provides significant advantages in terms of design flexibility, cost reduction, and the ability to produce components with high complexity that are difficult to achieve with traditional manufacturing methods. The research process begins with creating a digital design using CAD (Computer-Aided Design) software. The material used is ABS (Acrylonitrile Butadiene Styrene) filament, which is known for its strong mechanical properties and resistance to maritime conditions. The prototype of the water jet propulsion was then produced using a 3D printer. The results showed that 3D printing of ABS filament allows it to be used as an impeller component with a maximum tensile strength of 24 Mpa which is stated to be safe because the maximum stress that occurs in the impeller when working is 18.73 Mpa. The performance analysis of the resulting water jet propulsion reached 571 cm/s indicating increased efficiency and operational stability. The conclusion of this study is that 3D printing technology is effective and efficient in designing and building water jet propulsion, offering an innovative solution that has the potential to improve the performance and efficiency of the maritime industry.